2006
DOI: 10.1111/j.1365-294x.2006.03114.x
|View full text |Cite
|
Sign up to set email alerts
|

Convergence, constraint and the role of gene expression during adaptive radiation: floral anthocyanins in Aquilegia

Abstract: Convergent phenotypes are testament to the role of natural selection in evolution. However, little is known about whether convergence in phenotype extends to convergence at the molecular level. We use the independent losses of floral anthocyanins in columbines (Aquilegia) to determine the degree of molecular convergence in gene expression across the anthocyanin biosynthetic pathway (ABP). Using a phylogeny of the North American Aquilegia clade, we inferred six independent losses of floral anthocyanins. Via sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 52 publications
6
118
2
Order By: Relevance
“…As a result, when species from such clades experience the same selective conditions, they may adapt in genetically and developmentally similar ways (Haldane 1932;Gould 2002;Hoekstra 2006). Recent studies have provided many examples in which parallel phenotypic change in closely related species (or populations of the same species) is caused by similar genetic changes in a wide range of organisms and traits (e.g., Sucena et al 2003;Colosimo et al 2005;Hoekstra et al 2006;Protas et al 2006;Shapiro et al 2006;Whittall et al 2006;Baxter et al 2008;Gross et al 2009;Chan et al 2010; of course, this is not always the case: sometimes convergent phenotypic evolution is accomplished by different genetic changes, even in closely related species [e.g., Hoekstra and Nachman 2003;Wittkopp et al 2003;Hoekstra et al 2006;Kingsley et al 2009] Bossuyt and Milinkovitch 2000;Ruedi and Mayer 2001;Stadelmann et al 2007), and the examples that have been suggested require further examination to assess the extent of species-forspecies matching (Losos 2009). Radiations occurring on different continents usually will be accomplished by distantly related clades that are, for reasons just discussed, likely to diversify in different ways (Pianka 1986;Cadle and Greene 1993;Losos 1994).…”
Section: Replicated Adaptive Radiation Usually Occurs Amongmentioning
confidence: 99%
“…As a result, when species from such clades experience the same selective conditions, they may adapt in genetically and developmentally similar ways (Haldane 1932;Gould 2002;Hoekstra 2006). Recent studies have provided many examples in which parallel phenotypic change in closely related species (or populations of the same species) is caused by similar genetic changes in a wide range of organisms and traits (e.g., Sucena et al 2003;Colosimo et al 2005;Hoekstra et al 2006;Protas et al 2006;Shapiro et al 2006;Whittall et al 2006;Baxter et al 2008;Gross et al 2009;Chan et al 2010; of course, this is not always the case: sometimes convergent phenotypic evolution is accomplished by different genetic changes, even in closely related species [e.g., Hoekstra and Nachman 2003;Wittkopp et al 2003;Hoekstra et al 2006;Kingsley et al 2009] Bossuyt and Milinkovitch 2000;Ruedi and Mayer 2001;Stadelmann et al 2007), and the examples that have been suggested require further examination to assess the extent of species-forspecies matching (Losos 2009). Radiations occurring on different continents usually will be accomplished by distantly related clades that are, for reasons just discussed, likely to diversify in different ways (Pianka 1986;Cadle and Greene 1993;Losos 1994).…”
Section: Replicated Adaptive Radiation Usually Occurs Amongmentioning
confidence: 99%
“…Investigations in Ipomoea, as well as in Petunia, Antirrhinum and Mimulus, have all revealed that genetic changes associated with this transition are also regulatory, involving modification of transcription factors rather than enzyme-coding genes (Quattrocchio et al, 1999;Durbin et al, 2003;Schwinn et al, 2006;Whittall et al, 2006). The pattern of transcription factor mutations contrasts with that of spontaneous mutations, approximately half of which involve functional inactivation of enzyme-coding genes (Streisfeld and Rausher, 2011).…”
mentioning
confidence: 79%
“…Our study is not the first, however, to document distribution of floral colour polymorphism and monomorphism across several plant species. Published estimates range from 22% of species from a clade within Aquilegia (from [58]) and 36% of species in Polemoniaceae [9]. Other studies of cross-species patterns take an approach different from the one used here but still point to divergent selection as favouring pigment polymorphism [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Second, evolutionary transitions between pink and white may not occur at equal rates. Based on phylogenetic comparisons in a few well-studied lineages, floral anthocyanins are more likely to be lost within a lineage than to be gained [58,73]. Similarly, monomorphism should be easier to evolve from polymorphism than the inverse [12].…”
Section: Discussionmentioning
confidence: 99%